Asparagus dabieshanensis (Asparagaceae), a new species from Dabie Mountains, Central China - Yang, Jia-Xin; Zhu, Xin-Xin; Jia, Nan; Hu, Guang-Wan; Wang, Qing-Feng (Phytotaxa, 2024)
Asparagus dabieshanensis, a new species from the Dabie Mountains, Central China, is described and illustrated. Morphologically, it is similar to A. cochinchinensis (Lour.) Merr. and A. filicinus D. Don, but differs in having long and straight cladodes, and shorter pedicel than that of the last two species. Molecular phylogenetic analysis based on the combined four DNA markers (trnH-psbA, trnD-trnT, ndhF, phyC) indicated that the new species is a sister to A. cochinchinensis with strong support.